THE ROLE OF EVENTS IN SHAPING THE TOURIST ATTRACTIVENESS OF DESTINATIONS - Антонюк, Катерина; Лук’янець, Алла (SWorldJournal, 2025)
This article examines the role of events in shaping the tourism appeal of destinations. The authors emphasize that amidst growing competition in the tourism market, events are becoming a strategic tool for attracting tourists and enhancing regional compe